When Veto Power Defeats Humanity: The United States' Role in Blocking the Palestinian Resolution at the UN - Bayu Wijaya; Satrih Hasyim; Arfah Tjolleng (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to analyze the use of the United States veto power as an obstacle to the adoption of humanitarian resolutions concerning Palestine and to examine its implications for the effectiveness of the collective security system in international law. The research employs a normative legal method using conceptual and case approaches through library research of official documents and relevant scholarly literature. The novelty of this study lies in positioning the veto power as a structural barrier within international decision-making mechanisms rather than merely a foreign policy instrument. The findings reveal that the consistent use of veto in the Palestine issue has hindered the adoption of binding resolutions, weakened collective political pressure, and limited the effectiveness of civilian protection in situations of armed conflict. This condition creates tension between the formal legitimacy of the veto mechanism and the normative objective of humanitarian protection in the international system. The study concludes that the dominance of political interests in the use of veto contributes to a gap between international legal norms and their implementation, thereby requiring stronger global commitment to prioritize humanitarian protection in international decision-making processes.